Peripheral vascular manifestation in patients receiving an amphetamine analog: A case series. (February 2019) - Tan, GuangMing; Mintz, Ari J; Mintz, Bruce; Borges, Jorge C; Hines, Mary Deborah; Schainfeld, Robert M; Jaff, Michael R; Weinberg, Ido
Amphetamine and its related derivatives and analogues (ADRA) are highly addictive central nervous system stimulants that are used commonly in the treatment of attention-deficit/hyperactivity disorder and narcolepsy. These medications are associated with many side effects but reports of peripheral arterial manifestations associated with ADRA usage are scarce. We retrospectively reviewed the records of 16 patients (median age 37 years (IQR 31–47), 13 females) referred to a single tertiary referral service while receiving ADRA. Follow-up was available for a median of 3 years (IQR 3–4.5). The most common presentation (62.5%) was mild vasospastic symptoms involving the upper, lower or both extremities. Six patients developed severe manifestations including tissue loss and the need for lower extremity amputation. Most patients (75%) refused to stop the medication during follow-up. Underlying rheumatologic disorders were found in 25% of the patients, and the presence of rheumatologic disease seemed to be associated with more severe vascular manifestations. In conclusion, it is important to search for ADRA usage as part of the differential diagnosis of digital ischemia.